Quinolinamide-Enabled Nickel-Catalyzed Regio- and Diastereoselective γ,δ-Arylalkylation of Nonactivated Alkenes - Zhang, Lanlan; Zhao, Lei; Zhu, Yuqin; Wang, Chao (Synlett, 2023)
A quinolinamide-enabled nickel-catalyzed γ,δ-arylalkylation of homoallylic amines with aryl iodides and organozinc compounds has been developed. The cleavable quinolinamide directing group facilitates the stabilization of a five-membered nickelacycle, and enables the dicarbofunctionalization of nonactivated alkenes with excellently regio-, chemo-, and diastereoselectivity. The reaction with internal alkenes proceeds stereospecifically to provide valuable γ-alkyl-δ-aryl-substituted amines with two vicinal stereocenters. The scope of substrates and the utility of the protocol have been thoroughly studied.
Keywords: alkenes; directing group; aryalkylation; nickel catalysis; diastereoselectivity